La végétalisation de Paris vue au travers d’une carte : une capitale verte ? - Amélie Deschamps (M@ppemonde)
This article focuses on an online cartographic device offering a visualization of urban greening projects as part of the Parisian municipal policy. With a critical cartography approach, we show how the construction of the map, from design choice to data collection, participates in a discursive project, building an image of a green city to the French capital. The composition of the map with a mix of institutional and contributory data translates the ambiguity of the Parisian greening policy, between citizen participation and political instrumentalization.